1976
DOI: 10.1002/pssa.2210380147
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Nd3+ ions in garnet compounds forming in the Y2O3Ga2O3 system

Abstract: Detailed spectroscopic investigations are made for cubic (O h10–Ia3d) Nd3+ doped Y3Ga5O12 and YGaO3 garnet crystals, formed in the physico‐chemical Y2O3‐Ga2O3 system with sesquoxide relations 3:5 and 1:1. As result of absorption and luminescence spectra analysis, the Stark splittings of the lowest 4F3/2 and 4I9/2‐15/2 manifolds of the Nd3+ ions are determined with high accuracy. This allows to make reliable identification of induced transitions measured before in Y3Ga5O12–Nd3+ crystals. Some spectroscopic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…1. Just as that reported by Kaminskii et al [24], the Nd:YGG crystal grown by optical floating zone method used in the experiment also possesses an emis sion at about 1110 nm, and the laser at this wavelength should be realized by suitable suppressing the oscilla tion at 1.06 μm. Recently, Yu et al reported a laser diode pumped Nd:YGG crystal laser at 1110 nm for the first time.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…1. Just as that reported by Kaminskii et al [24], the Nd:YGG crystal grown by optical floating zone method used in the experiment also possesses an emis sion at about 1110 nm, and the laser at this wavelength should be realized by suitable suppressing the oscilla tion at 1.06 μm. Recently, Yu et al reported a laser diode pumped Nd:YGG crystal laser at 1110 nm for the first time.…”
Section: Introductionmentioning
confidence: 92%
“…Nd:YGG can be generated by replacing aluminum with gallium in the Nd:YAG. Previous studies on its spectral properties discovered that in the transition from the upper 4 I 11/2 manifold to the lower 4 F 3/2 [24][25][26]. The fluorescence spectra of Nd:YGG with a laser diode as pump source is shown 1 The article is published in the original.…”
Section: Introductionmentioning
confidence: 97%
“…The starting materials were prepared from the stoichiometric mixture of Nd 2 The mixture was sintered at 1100 1C for 10 h to complete the solid-state chemical reaction. Then the polycrystalline material was ground and loaded into a rubber membrane to fabricate the feed rod, the feed rod was vacuum treated and hydrostatically pressed to about 70 MPa.…”
Section: Crystal Growthmentioning
confidence: 99%
“…As an important part of solid-state lasers, the laser material is the key factor that determines the properties of lasers. Neodymium-(Nd) doped garnet crystals have been studied as excellent laser materials, including Y 3 Al 5 O 12 (YAG), Y 3 Ga 5 O 12 (YGG), Lu 3 Al 5 O 12 (LuAG), Gd 3 Ga 5 O 12 (GGG), Gd 3 Sc 2 Ga 3 O 12 (GSGG) and Y 3 Sc 2 Ga 3 O 12 (YSGG) due to their high optical quality, excellent heat conductivity and stable structure [1][2][3][4][5][6][7][8][9][10][11]. As the most important representative of garnet crystals, Nd-doped YAG has been one of the most widely used laser crystals and output power has reached tens of kilowatts [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Garnets are superior to many other classes of laser host materials because of the isotropy of their properties, high mechanical strength, and thermal conductivity, and good optical homogeneity. Many garnet crystals have been studied extensively as laser host materials, for example, Y 3 Al 5 O 12 (YAG), Y 3 Ga 5 O 12 (YGG), Gd 3 Ga 5 O 12 (GGG), Gd 3 Sc 2 Ga 3 O 12 (GSGG), Y 3 Sc 2 Ga 3 O 12 (YSGG), Ca 3 Ga 2 Ge 3 O 12 (CGGG) [5][6][7][8][9][10][11][12][13][14][15], etc.…”
Section: Introductionmentioning
confidence: 99%